Frontier issues in ecological economics - Lawn, Philip A.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2007)
Ecological economics formally emerged in the late 1980s in response to the failure of mainstream economic paradigms to deal adequately with the interdependence of social, economic and ecological systems. Frontier Issues in Ecological Economics focuses on a range of cutting-edge issues in the field of ecological economics and outlines plausible measures to achieve a more sustainable, just, and efficient world for all.
pt. 1. An introduction to ecological economics, sustainable development and the steady-state economy -- pt. 2. Sustainable development and natural capital -- pt. 3. Sustainable development indicators -- pt. 4. Sustainable development : theoretical and policy issues -- pt. 5. Sustainable development and the international dimension -- pt. 6. Conclusion.
Includes bibliographical references (p. 344-362) and index.
Keywords: Environmental economics; Sustainable development; Electronic books